Unlocked No (1) HXBXD. - Debbaut, Jan; Hartzema, Esther; Jansma, Esther; Meijer, W.; Spaninks, Angelique; van Schijndel, Marieke (Eindhoven : Kunstzaken Rabobank Nederland Eindhoven, 2001)
Andriesse, Jan ; Baerveldt, Erzsébet ; Appel, Karel ; Birza, Rob ; Bolink, Merijn ; Broek, Hans ; Brouwn, Stanley ; Claassen, Tom ; Constant ; Daniels, René ; Dibbets, Jan ; Dolron, Désirée ; Framis, Alicia ; Geelen, Guido ; van Elk, Ger ; van Golden, Daan ; Gudmundsson, Sigurdur ; Hendriks, Rosemin ; Hermans, Benoît ; Klein, Micha ; Koelewijn, Job ; Kraijer, Juul ; Lamers, Kiki ; Atelier van Lieshout ; Manders, Mark ; Meerman, Bas ; Mol, Pieter Laurens ; Mulders, Marc ; Preesman, Avery ; Roosen, Maria ; Schleiffert, Charlotte ; Scholte, Rob ; Ulay ; Vanderheyden, JCJ ; Verkerk, Emo ; Vermeule, Koen ; Versloot, Ronald ; van Vught, Reinoud ; Visch, Henk
Biog. van Erzsébet Baerveldt p.126
Biog. van Ger Van Elk p. 24
Biog. van Henk Visch p. 70
Engels & Nederlands
boek
Keywords: Nederland